2008
DOI: 10.1016/j.exger.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Does age influence loss of heterozygosity?

Abstract: The striking correlation between advanced age and an increased incidence of cancer has led investigators to examine the influence of aging on genome maintenance.Because loss of heterozygosity (LOH) can lead to the inactivation of tumor suppressor genes, and thus carcinogenesis, understanding the affect of aging on this type of mutation event is particularly important. Several factors may affect the rate of LOH, including an increase in the amount of DNA damage, specifically double-strand breaks (DSB), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
3
10
1
2
Order By: Relevance
“…However, our results indicate that without a cost of sex (c ¼ 1), this effect is important only for rates of mitotic gene conversion of the order $10 À3 and rates of mitotic crossing over of the order $10 À2 (Figures 4 and 5). These values are higher than most available estimates on rates of loss of heterozygosity (Tischfield 1997;Shao et al 1999;Holt et al 1999;Omilian et al 2006;Mandegar and Otto 2007;Carr and Gottschling 2008), suggesting that the consequence of such events on the evolution of sex in the presence of deleterious mutations may be limited. Furthermore, we found that mitotic gene conversion does not affect much our results when sex is costly (see Appendix SF).…”
Section: à4contrasting
confidence: 46%
See 1 more Smart Citation
“…However, our results indicate that without a cost of sex (c ¼ 1), this effect is important only for rates of mitotic gene conversion of the order $10 À3 and rates of mitotic crossing over of the order $10 À2 (Figures 4 and 5). These values are higher than most available estimates on rates of loss of heterozygosity (Tischfield 1997;Shao et al 1999;Holt et al 1999;Omilian et al 2006;Mandegar and Otto 2007;Carr and Gottschling 2008), suggesting that the consequence of such events on the evolution of sex in the presence of deleterious mutations may be limited. Furthermore, we found that mitotic gene conversion does not affect much our results when sex is costly (see Appendix SF).…”
Section: à4contrasting
confidence: 46%
“…Such loss of heterozygosity (LOH) events represent a frequent step in oncogenesis (Gupta et al 1997;Tischfield 1997;Hagstrom and Dryja 1999;Holt et al 1999;Sieber et al 2002), which may partly explain why mitotic crossing over is suppressed. Nevertheless, mitotic recombination is thought to occur at rate $0.8 3 10 À4 per cell per generation in yeast (Mandegar and Otto 2007 and references therein), while LOH is often observed at a frequency of 10 À4 -10 À5 in normal cells in vivo, in mice and in humans (Tischfield 1997;Holt et al 1999;Shao et al 1999;Carr and Gottschling 2008). Furthermore, Chamnanpunt et al (2001) measured rates of mitotic gene conversion ranging from 3 3 10 À2 to 10 À5 in hybrids of the oomycete Phytophthora sojae.…”
Section: à10mentioning
confidence: 99%
“…Similarly, the number of DNA strand breaks and time required for their repair is significantly influenced by ageing (22,23). Double-strand DNA breaks can even participate to the loss of heterozygosity in the elderly and can be important for cancerogenesis (24,25). The total number of mutations acquired during ageing is extremely high, and robust genomic technologies demonstrated that 3,000-13,000 genes per genome can be affected by 5,000-50,000 mutations (26).…”
Section: Biological Background Of Ageing and Impact On Cancer Formationmentioning
confidence: 99%
“…While most spontaneous LOH in diploid yeast occurs primarily through mitotic recombination (Acuna et al 1994), all the same types of LOH found in tumors are also observed in yeast. In addition, an LOH event in yeast can be easily classified as either reciprocal (LOH occurs in both cells) or nonreciprocal (one cell undergoes LOH while the other remains heterozygous) (reviewed in Carr and Gottschling 2008). This has facilitated a better mechanistic understanding of LOH events.…”
mentioning
confidence: 99%
“…Patients who were heterozygous at the Rb locus, with one wild-type allele and one nonfunctional allele, had a high incidence of tumors that had lost the wild-type allele of Rb in somatic cells. There are several mechanisms by which the normal allele of Rb could become nonfunctional, but two pathways predominated to inactivate the wild-type allele: loss of part or all of the chromosome (a hemizygous state) or a recombination event that replaced the wild-type allele with the mutant allele from the homologous chromosome (a homozygous state) (reviewed in Carr and Gottschling 2008). These genetic changes became known as loss of heterozygosity (LOH) events.…”
mentioning
confidence: 99%